Mieruko-chan. 1 - Izumi, Tomoki (Yen Press, 2020)
"A normal girl was living a normal life--until she wasn't. One day, she could see... everything. What's a girl to do when hideous monsters appear no matter which way she turns? And on top of that, nobody else can see them! Obviously, there's only one thing that makes sense--ignore them. Kinda hard to put theory into practice, though, when the ghosts know she's watching..."--Provided by publisher.